Coexistence of Polycystic Ovary Syndrome and Endometriosis in Women with Infertility. Issue 2 (April 2014) - Holoch, Kristin J.; Savaris, Ricardo F.; Forstein, David A.; Miller, Paul B.; Higdon, H. Lee; Likes, Creighton E.; Lessey, Bruce A.
Purpose: The aim of this study was to investigate if there is a higher incidence of endometriosis in patients with polycystic ovary syndrome (PCOS), compared with normal fertile controls. Material and methods: Women with PCOS according to Rotterdam criteria, with infertility and/or pelvic pain, were identified (n = 104), and together with fertile women seeking bilateral tubal ligation (n = 111), they were submitted to laparoscopy at the Greenville Hospital System or the University of North Carolina at Chapel Hill. A biopsy was performed in 40 patients with PCOS to confirm or not endometriosis. Results: Age was similar in both groups (control: 29.7 ± 0.5 years; PCOS: 29.6 ± 0.4). The incidence of suspected endometriotic lesions in controls and PCOS patients was 12.6% (95% confidence interval [95% CI], 7.6%-20%) and 74% (95% CI, 64.8%-81.5%), respectively; with an odds ratio of 19.7 (95% CI, 9.6-40.2) of finding endometriosis in PCOS (p<0.0001). Our results were similar when endometriosis was confirmed by pathology report. Of the PCOS patients with endometriosis, 76% had endometriosis stage I or II, according to the revised American Society for Reproductive Medicine criteria. Conclusions: In this case-control study, a significant association between endometriosis and women with PCOS with pelvic pain and/or infertility was found. The majority of endometriotic lesions (76%) were stage I or II.